Vesicular-Arbuscular Mycorrhizal colonization and growth of tomato (Lycopersicon esculentum) in autoclaved soil - S., Manian; Thomson T., Edathil; K., Udaiyan (Universiti Putra Malaysia Press, 1995)
The effect of autoclaving soil an uesicular-arbuscular mycorrhizal (VAAl) Jungal colonization and biomass production of tomato (Lycopersicon esculentum Mill) was assessed in pot experiments under greenhouse conditions. Four treatments were given viz., (1) VAM-free plants in autoclaued soil, (2) VAM plants in autoclaued soil, (3) VAM plants in autoclaved soil amended with VAM-free filtrate of non-autoclaved soil, and (4) VAM plants in non-auloclaved soil. The VAM plants grown in non-autoclaued soil showed the highest root colonization of 87.78% while those under (2) and (3) showed only 55.11 % and 56.94% respectiuely. On the other hand, significantly higher shoot length (105.4 cm2/plant), wtal kaJ area (740.3 cm2/plant) and biomass (8.43 g/plant) were obtained in VAM plants grown in autoclaved soiL VAM-free plants in autaclaved sail had reduced growth. In treatments 3 and 4 plant growth was intermediate. The results indicate that VAM colonization and sporulation were favoured under natural conditions, but VAM plants under autoclaved soil conditions produced maximum growth.